DNA repair pathways as targets for cancer therapy. - Helleday, T; Petermann, E; Lundin, C; Hodgson, B; Sharma, R (2008)
DNA repair pathways can enable tumour cells to survive DNA damage that is induced by chemotherapeutic treatments; therefore, inhibitors of specific DNA repair pathways might prove efficacious when used in combination with DNA-damaging chemotherapeutic drugs. In addition, alterations in DNA repair pathways that arise during tumour development can make some cancer cells reliant on a reduced set of DNA repair pathways for survival. There is evidence that drugs that inhibit one of these pathways in such tumours could prove useful as single-agent therapies, with the potential advantage that this approach could be selective for tumour cells and have fewer side effects.